Economic globalization and financial development in East Asia: a panel cointegration and causality analysis - Law, Siong Hook; Wan Ngah, Wan Azman Saini; Tan, Hui Boon (Taylor & Francis, 2014)
This study examines the role of economic globalization in financial development in eight East Asian economies. The heterogeneous panel cointegration test reveals that cointegration is present among economic globalization, institutions, financial development, real gross domestic product per capita, and financial reforms. The Granger causality test results indicate that economic globalization has a significant causal influence on institutional quality, and institutional reforms have in turn facilitated and supported financial development, in particular of the banking sector in East Asia. Economic globalization is also found to have a favorable causal impact on stock market development without going through the institutional quality channel.